1995
DOI: 10.1038/jcbfm.1995.33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pentylenetetrazol-Induced Status Epilepticus on Local Cerebral Blood Flow in the Developing Rat

Abstract: Summary:The quantitative autoradiographic e4Cl iodoantipyrine technique was applied to measure the ef fects of a 30-min period of pentylenetetrazol (PTZ) induced status epilepticus (SE) on local cerebral blood flow (LCBF) in rats 10 (PlO), 14 (PI4), 17 (P17), and 21 (P21) days after birth. The animals received repetitive, timed injections of subconvulsive doses of PTZ until SE was reached. At PIO, SE induced a 32 to 184% increase in the rates of LCBF affecting all structures studied. In PI4-and PI7 PTZ-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
5
11
0
Order By: Relevance
“…Our inulin data demonstrated that BBB integrity was not altered, 16 suggesting that the increase in diazepam uptake is more likely due to enhanced cerebral blood flow. This is consistent with the fact that diazepam is often used as a marker of cerebral blood flow 16 and that this parameter increases following convulsive seizures 15 . Interestingly, the brain uptake of diazepam was not enhanced in the mouse model of absence epilepsy, which may be attributed, in part, to the fact that cerebral blood flow does not increase in absence epilepsy but, rather, decreases 17,18 …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our inulin data demonstrated that BBB integrity was not altered, 16 suggesting that the increase in diazepam uptake is more likely due to enhanced cerebral blood flow. This is consistent with the fact that diazepam is often used as a marker of cerebral blood flow 16 and that this parameter increases following convulsive seizures 15 . Interestingly, the brain uptake of diazepam was not enhanced in the mouse model of absence epilepsy, which may be attributed, in part, to the fact that cerebral blood flow does not increase in absence epilepsy but, rather, decreases 17,18 …”
Section: Discussionsupporting
confidence: 81%
“…The brain uptake of diazepam, an AED that permeates the BBB via passive diffusion, was significantly enhanced following PTZ administration. This enhanced exposure of diazepam after acute seizure may be due to a disruption in the BBB architecture or an enhancement in cerebral blood flow, two phenomena that have been observed in rodents after PTZ‐induced seizures 1,15 . Our inulin data demonstrated that BBB integrity was not altered, 16 suggesting that the increase in diazepam uptake is more likely due to enhanced cerebral blood flow.…”
Section: Discussionsupporting
confidence: 49%
“…1992; Pereira de Vasconcelos et al . 1992, 1995). It consisted of an injection of the first dose of 40 mg/kg PTZ, followed by 20 mg/kg 10 min later and then, every 10 min, additional i.p.…”
Section: Methodsmentioning
confidence: 99%
“…We showed previously that PTZ‐induced SE leads to acute and long‐term age‐specific changes in cerebral metabolism and blood flow (Pereira de Vasconcelos et al . 1992, 1995; Hussenet et al . 1995; Nehlig & Pereira de Vasconcelos 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In other models of SE (e.g., pentylenetetrazol), no neuronal damage occurs even in P21 rats after approximately 80 minutes of seizure activity. In that model, the lack of neuronal damage may arise from relatively moderate metabolic increases compared with those recorded in the lithium-pilocarpine model and the maintenance of coupling between LCMR glc and LCBF rates (Pereira de Vasconcelos et al, 1992Vasconcelos et al, , 1995.…”
Section: A Pereira De Vasconcelos Et Al 202mentioning
confidence: 99%